2014
DOI: 10.1002/jcc.23676
|View full text |Cite
|
Sign up to set email alerts
|

Valence state parameters of all transition metal atoms in metalloproteins—development of ABEEMσπ fluctuating charge force field

Abstract: To promote accuracy of the atom-bond electronegativity equalization method (ABEEMσπ) fluctuating charge polarizable force fields, and extend it to include all transition metal atoms, a new parameter, the reference charge is set up in the expression of the total energy potential function. We select over 700 model molecules most of which model metalloprotein molecules that come from Protein Data Bank. We set reference charges for different apparent valence states of transition metals and calibrate the parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 118 publications
(128 reference statements)
0
52
0
2
Order By: Relevance
“…Further extending their work on TMs, Yang et al fit the reference charge, electronegativity, and chemical hardness parameters for 3d, 4d, and 5d TMs in the ABEEMσπ force field. 852 More than 700 structures were contained in the training set. The target values were the Mulliken charges obtained at the HF/STO-3G (for 3d and 4d TM complexes) or HF/CEP-4G (for 5d TM complexes) level of theory, and the dipole moments calculated using larger basis sets.…”
Section: Classical Modeling Of Metal Ions: the Polarizable Modelmentioning
confidence: 99%
“…Further extending their work on TMs, Yang et al fit the reference charge, electronegativity, and chemical hardness parameters for 3d, 4d, and 5d TMs in the ABEEMσπ force field. 852 More than 700 structures were contained in the training set. The target values were the Mulliken charges obtained at the HF/STO-3G (for 3d and 4d TM complexes) or HF/CEP-4G (for 5d TM complexes) level of theory, and the dipole moments calculated using larger basis sets.…”
Section: Classical Modeling Of Metal Ions: the Polarizable Modelmentioning
confidence: 99%
“…Wilson and Ichikawa and Torrent‐Sucarrat and coworkers pointed out that the charge transfer between atoms in a molecule is overestimated by using the polarization basis sets. Huzinaka et al, Jakalian et al, Watanabe et al, and our group have shown that the use of higher levels of basis sets overestimates the overlap between their respective basis functions belonging to two atoms in a molecule. Bayly and his coworkers pointed out that when the 6‐31G* basis set is used, the polarity of a molecule calculated by the partial charges is overestimated by 10%–15% .…”
Section: Computational Detailsmentioning
confidence: 66%
“…The detailed description of the QM/MM(ABEEM) method and free energy perturbation theory can be found in our previous articles, and some ABEEMσπ parameters of ruthenium complexes were determined by our previous work, while others were calibrated and determined through a regression and least‐squares optimization procedure. The details were described in our previous articles . All ABEEMσπ parameters are listed in Supporting Information Table S1.…”
Section: Computational Detailsmentioning
confidence: 99%
“…They are obtained by fitting the QM Mulliken charge distribution through a regression and least-squares optimization procedure. [39,40] When H 2 O molecule bonds with Ru atom, the O atom is named 108144 and the H atom is named 101144 in order to distinguish from other water molecules. [31,32,35].…”
Section: Qm/mm(abeem) Methodologymentioning
confidence: 99%